Emotional labor and discretionary behaviors: Exploring the mediating and moderating effects of felt inauthenticity and emotional exhaustion - ANG, Yang Ting (Institutional Knowledge at Singapore Management University, 2017)
The service industry is a growing sector in most countries and emotional labor is a major component of service employees’ jobs. As such, it is important to understand how emotional labor influences employee discretionary behaviors such as counter-productive workplace behaviors (CWBs) and organizational citizenship behaviors (OCBs), both of which affect the well-being of employees and organizations. This dissertation presents two studies that examined the mechanisms underlying, and boundary conditions surrounding, emotional labor and employee discretionary behaviors. Drawing on theories and research regarding ego depletion, inauthenticity, and behavior consistency, this paper proposed a theoretical model that hypothesized how two potential mechanisms (i.e., felt inauthenticity and emotional exhaustion) work interactively to connect emotional labor with discretionary behaviors. Two multi-wave studies consisting of three measurement periods of 240 (Study 1) and 441 (Study 2) employees conducted on MTurk provided partial support for the hypothesized model. As hypothesized, felt inauthenticity and emotional exhaustion interacted to influence the two types of counterproductive workplace behaviors (CWBs). As such, the indirect effects between surface acting and CWBs through felt inauthenticity were moderated by emotional exhaustion. More specifically, the indirect effects were positive and stronger at low levels of emotional exhaustion but weaker at high levels of emotional exhaustion.